2016
DOI: 10.1021/jacs.6b03113
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Active and Regioselective Catalysts for the Copolymerization of Epoxides with Cyclic Anhydrides: An Unanticipated Effect of Electronic Variation

Abstract: Recent developments in polyester synthesis have established several systems based on zinc, chromium, cobalt, and aluminum catalysts for the ring-opening alternating copolymerization of epoxides with cyclic anhydrides. However, to date, regioselective processes for this copolymerization have remained relatively unexplored. Herein we report the development of a highly active, regioselective system for the copolymerization of a variety of terminal epoxides and cyclic anhydrides. Unexpectedly, electron withdrawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
128
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 64 publications
(21 reference statements)
6
128
0
Order By: Relevance
“…The epoxide/CA copolymerization has been considered to be a promising route to structurally diverse polyesters . Recently, a variety of well‐defined zinc, magnesium, aluminum, chromium, Co, manganese, and iron complexes have been reported as efficient catalysts. In addition, Lu and coworkers developed biarylene‐linked bimetallic catalysts to achieve high activity and enantioselectivity via proximity effect …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epoxide/CA copolymerization has been considered to be a promising route to structurally diverse polyesters . Recently, a variety of well‐defined zinc, magnesium, aluminum, chromium, Co, manganese, and iron complexes have been reported as efficient catalysts. In addition, Lu and coworkers developed biarylene‐linked bimetallic catalysts to achieve high activity and enantioselectivity via proximity effect …”
Section: Resultsmentioning
confidence: 99%
“…NMR spectroscopic analysis of the obtained copolymer revealed the completely alternating structure. It is noteworthy that dinuclear complex ( R,R , S,S )‐ 1 demonstrated much higher catalytic activity than the mononuclear Co–salen complex which has been reported as a highly active catalyst . Thereby, proximity effect would also operate in this copolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt Salcy [bis(salicylaldimine)] complexes featuring nucleophilic axial groups [(Salcy)Co III X; X=halides, carboxyl, etc.] are among the most investigated catalysts for the copolymerization, wherein the alternative insertion of anhydrides and epoxides is directly correlated to the reversible formation and dissociation of the Co−O bonds (Scheme A) . Relative to the polar Co−O bonds, Co−C bonds tend to break homolytically to generate carbon‐based radicals as is known to occur, for instance, in the biological action of vitamin B12 .…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing research in this field, we developed mononuclear chromium complexes with such [ONSO] type ligands ([ONSO]CrX) and found that [ONSO]CrX complexes efficiently mediate the ring‐opening copolymerization (ROCOP) of epoxides with norbornene anhydride or carbon dioxide assisted by Lewis base or onium salts, giving the corresponding polyester and polycarbonate, respectively. Moreover, many reports have demonstrated that some dinuclear metal complexes show high catalytic activity in comparison with mononuclear analogues for the same polymerization . To our best knowledge, there are no reports on the synthesis and application of bimetallic complexes supported by [ONSO] type ligands in the catalytic copolymerization of epoxides with anhydrides.…”
Section: Introductionmentioning
confidence: 99%